The Effect of Competence and Compensation on Student Satisfaction and Its Impact on the Performance of Senior High Schools in Pamulang District, South Tangerang City - Rahman Faisal; Lukman Anthoni; Darul Fahmi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the effect of teacher competence and compensation on student satisfaction and its impact on school performance at senior high schools in Pamulang District, South Tangerang City. The study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to student respondents and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The results indicate that teacher competence has a positive and significant effect on student satisfaction, with a coefficient of 0.223, a T-statistic of 3.176, and a P-value of 0.002. Teacher competence also has a positive and significant effect on school performance, with a coefficient of 0.593, a T-statistic of 7.145, and a P-value of 0.000. Furthermore, compensation has a highly significant positive effect on student satisfaction, with a coefficient of 0.747, a T-statistic of 11.050, and a P-value of 0.000. Compensation also has a positive and significant effect on school performance, with a coefficient of 0.472, a T-statistic of 3.257, and a P-value of 0.001. However, student satisfaction shows a significant but negative effect on school performance, with a coefficient of -0.426, a T-statistic of 2.781, and a P-value of 0.006. The findings also reveal that student satisfaction significantly mediates the relationship between teacher competence and compensation and school performance, but with a negative direction. These findings indicate that improving student satisfaction needs to be balanced with academic quality standards to maintain overall school performance.